Cofradía: continuity and transformation of Andean society - Celestino, Olinda (1982)
In the framework of an ethnically, culturally and economically multi-differentiated society -post-colonial Peru- we try to analyze the processes of installation, integration and generalization of a particular institution: the religious brotherhood, and above all the modalities of its adaptation and transformations in The specific world of the Andean peasant in the central region of Peru. This institution of European origin and long history, with great apogee in the Western Middle Ages, was introduced as a missionary initiative by the Spanish shortly after the conquest; it was characterized by bringing together a large number of lay people for the purpose of practicing Catholic worship and mutual aid and were imposed according to the model of brotherhoods and "charges" that functioned in Spain in the 16th century.